Peningkatan Pemahaman Konsep Matematika Siswa Kelas I Dalam Mengurutkan Bilangan Melalui Media Bola Bilangan - Indra Prastianing Zahro; Richa Ria Anika; Diana Ermawati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research aims to improve students' understanding of ordering numbers in mathematics learning in class 1 of SDN 3 Undaan Lor through number balls. The method used in this research is Classroom Action Research (PTK). This research data collection technique uses tests and documentation. The data analysis technique used uses quantitative and qualitative data. The research subjects were all 26 students in class 1 of SD 3 Undaan Lor. The results of the research show that there is an increase in students' understanding of mathematical concepts in ordering numbers using number ball media which has proven to be effective, this is proven by the results of the percentage of data obtained during the pre-cycle, namely 38% in the poor category, increasing to 69% in the good category in the first cycle, then increased to 88% with a very good category in cycle 2. Increasing students' understanding in ordering numbers in mathematics learning in class 1 of SDN 3 Undaan Lor through number balls can increase by fulfilling the predetermined success indicators, namely 85%, so that this research is declared complete.